Qualitative Phytochemical ScreeningandIn VitroAntibacterialActivitiesof Crude Akaziraruguma Leaf Extracts - Cyuzuzo Callixte; Heny Arwati; Dusabimana Jean Damascene (Indian Journal of Forensic Medicine & Toxicology, 2021)
The resistance of pathogenic bacteria is a global health dynamic and the time is nowtofind alternativesolutions from plant secondary metabolites.Ageratum conyzoidesL. is a plant known as akazirarugumain Rwandaand used to treat wounds and ulcers. This study aimedto evaluate the phytochemical profileand germicidal efficacy of ethanolic and aqueous leaf extracts of Ageratum conyzoides L. grown inRwasave wetland.Theleaves were collected and dried under the shed for 10 days, blended into powderby electric blender and macerated with water and 96% ethanol. Phytochemical screening wasperformedby followingthe standard procedures and antibacterial activity of the extracts wasexamined by agar welldiffusion method and the inhibition zones were recorded.Phytochemical screening revealed the presence ofdifferent secondary metabolites including alkaloids, tannins, flavonoids, steroids, terpenoids and saponins. In this assessment,aqueous and ethanolic extracts exhibited significant inhibitory activity against testedpathogens with inhibition zones that ranging from6±0.9 mm to 20±0.5 mm of diameter. The minimuminhibition concentrations range between 0.47 mg/mL and 15.00 mg/mL.The resultsconfirm that the leavesof akazirarugumacould be the credible source ofantibacterial agents that should be used for therapeuticpurposes and in production of pharmaceuticals.